Current Knowledge on Factor V Leiden Mutation as a Risk Factor for Recurrent Venous Thromboembolism: A Systematic Review and Meta-Analysis - Eppenberger, Daria; Nilius, Henning; Anagnostelis, Betsy; Huber, Carola A.; Nagler, Michael (Frontiers in Cardiovascular Medicine, 2022)
Background Thrombophilia screening is widely done in clinical practice, and it is claimed that the extent of venous thromboembolism (VTE) recurrence risk in patients with common defects is still not fully understood. Aim We aimed to summarize data of all observational studies prospectively assessing the association of heterozygous factor V Leiden (FVL) mutation and recurrent VTE in patients with VTE, and to calculate pooled relative risks (RR), overall and in various subgroups. Methods We searched MEDLINE and EMBASE databases for cohort studies prospectively assessing VTE recurrence in patients with and without FVL mutation (PROSPERO: CRD42021182800). Data were extracted on cohort and study-level. The methodological quality was assessed using the Newcastle-Ottawa Scale (NOS). RR were calculated overall and in subgroups using a random-effects model. Results From 31 cohorts, 24 studies were finally included summarizing 13,571 patients. Heterozygous FVL mutation was identified in 2,840 individuals (21%). The methodological quality was estimated to be high in 20 studies (83%). The overall RR was 1.46 (95% CI: 1.31, 1.64), consistent across subgroups. Conclusions Pooling all high-quality epidemiological data, the risk of recurrent VTE was increased by 46% in patients with heterozygous FVL mutation. Against the background of established risk factors, the FVL mutation plays only a marginal role in the risk assessment for recurrent VTE.